Peace strengthens human prosperity: Islam and world peace - Kayadibi, Saim (Association of Muslim Social Scientists, 2010)
This conference, organized by the Faculty of Usuluddin at Sultan Sharif Ali Islamic University (UNISSA), was held on 24-25 February 2010 at the Rizqun International Hotel in Gadong, Brunei. The 119 local and 40 international participants presented 78 working papers. Local and international media outlets and representatives of government bodies, as well as officers from the Department of Community Development, the Ministry of Religious Affairs’ Syariah Affairs Department, and the Brunei Economic Development Board, also attended. One of the main objectives was to clear up misconceptions about Islam in order to bridge the gap and strengthen relationships and cooperation between Muslim and western countries.